Skin capillary density in pregnancy induced hypertension and normotensive pregnant participants - Kumar, Mahendra; Bansal, Vandana; Mhatre, Pravin N.; Khopkar, Uday (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Pre-eclampsia is a vascular related disorder of pregnancy, Despite the increasing research efforts in the field, the etiology and pathogenesis of this disorder remain elusive, resulting in failure to develop specific screening, preventive and treatment strategies. Peripheral vasodilatation and angiogenesis are critical components of physiological adaptation in normal pregnancy. Women who have later developed preeclampsia had significant structural capillary density rarefaction early in the pregnancy before the onset of preeclampsia. Methods: Case control, comparative study was carried out at our institute. 30 pregnant participants were recruited in each group after satisfying the inclusion criteria. Data was collected by using dermatoscope (200X magnification). Statistical analysis was done by non-parametric test- Mann-Whitney test as blood pressure was not normally distributed among participants. Spearman’s correlation coefficient was used to make correlation between skin capillary densities and blood pressures. Results: On applying Mann-Whitney test, mean rank for systolic and diastolic blood pressure at 20 weeks for both groups were not significant statistically, mean rank for systolic and diastolic blood pressure between 28-36 weeks of gestation for both groups were significant statistically. After testing, skin capillary density came significantly less in hypertensive group as compare to normotensive pregnant participant of same gestational ages. Spearman’s correlation coefficient came negative for systolic and positive for diastolic blood pressure at 28-36 weeks of gestation. Conclusions: Authors conclude that estimating the skin capillary density provides a potentially useful clinical marker in the prediction of preeclampsia and dermatoscope is an especially attractive clinical tool.